Pengaruh Partisipasi Anggaran, Penekanan Anggaran, Asimetri Informasi terhadap Budgetary Slack pada SKPD Kota Samarinda - Heny Kusniawati; Ibnu Abni Lahaya (AKUNTABEL, 2017)
This study aims to examine the effect of budget participation, budgeting emphasis, and information asymmetry on budgetary slack on SKPD of Samarinda using multiple linear regression model with SPSS 23 software. The population in this research is all structural officials of SKPD Kota Samarinda. Sample selection using purposive sampling method. The selected samples are the parties who participated in the preparation of budget activities program which includes the Head Office, Sub-Head of Finance, Planning Head and Planning Staff at 36 SKPD in Samarinda, so the sample amounted to 112 respondents. The findings in the study are budget participation has a negative but not significant effect on budgetary slack on SKPD Samarinda this is because of alignment between employee goals and SKPD high. Budget emphasis has significant positive effect on budgetary slack on SKPD of Samarinda City. This is because budget targets serve as performance benchmarks so that employees can loosen the budget that makes budget targets accessible. Information asymmetry has a positive but insignificant effect on budgetary slack on SKPD Kota Samarinda. This can happen because of a clear regulation so that the information reported by a subordinate to the boss is in accordance with what really happened.Keywords: Budgetary Participation, Budget Emphasis, Information Asymmetry and Budgetary Slack